KEDUDUKAN JANDA DALAM HUKUM WARIS ADAT PADA MASYARAKAT PARENTAL - Eka Susylawati (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
The field of succession law in Indonesia up to now prevails lawpluralism in which Islamic succession, custom succession andwestern succession law (Burgerlijk Wetboek) exist in society.Among those succession laws, the custom succession one is themost dominant law in society. The custom law that has dynamiccharacteristics also influences to the status of widow to thelegacy oh her late husband, that from time to time it changes. Inparental society, in the early (before RI freedom), a widow wasnot a heir, then the next development, the widow inherit thelegacy of her late husband although the change has not receivedwell. The cause of the change is the awareness of society inrespecting the status of the widow and also because the mostIndonesian society are Islam that develops the customsuccession law influenced by Islamic law.